Zr-containing precipitate evolution and its effect on the mechanical properties of Cu–Cr–Zr alloys - Yibo Du; Yanjun Zhou; Kexing Song; Tao Huang; David Hui; Haitao Liu; Chu Cheng; Jingzhao Yang; Liye Niu; Huiwen Guo (Journal of Materials Research and Technology, 2021)
The present work investigates the Zr-containing precipitate evolution and its effect on the mechanical properties of a Cu–Cr–Zr alloy after solution treatment at 1253 K for 2 h and aging at 763 K for 0–6 h. The results show that the precipitation sequence of the Zr-containing precipitates in the Cu–Cr–Zr alloy is supersaturated solid solution→Zr-rich atomic clusters→Cu5Zr phase. Zr atoms first segregate at the {111} crystal plane of the copper and form coherent Zr-rich atomic clusters during the aging process, which are composed of Zr-rich atoms monolayers and exhibit plate-shaped. Some of the Zr-rich atomic clusters is transformed into the more stable phase of Cu5Zr phase as the aging time increases, the habit plane of which is the {111}Cu crystal plane. The contribution of Zr-rich atomic clusters and Cu5Zr precipitates to the yield strength of the alloy is calculated by coherency strengthening and Orowan strengthening, respectively. The total yield strength is very close to the experimentally measured strength.